Risk factors of early and late preterm birth - Oli, Upanish; Upreti, Radhika; Ojha, Neebha; Singh, Meeta (Nepal Medical College Journal, 2021)
Preterm birth (PTB) is one of the major causes of morbidity in newborn. The aim of this study was to estimate the prevalence and to compare the associated risk factors of early and late PTB. This was a hospital-based cross sectional study conducted in 2016/2017. Women, 271, having PTB at 28-33+6 weeks period of gestation was taken as early PTB and 34-36+6 were taken as late PTB. Data was collected using semi-structured questionnaire, patients’ record book, adopting face- to - face interview technique and clinical examination. The annual prevalence of PTB was 7.25% of which 11% were <28+0 weeks, early PTB was 32% and late PTB was 57%. Mother with school education were 2.0 times more likely to have early preterm births than those having higher education (P-value: 0.005, COR: 2.061,95% CI:1.234-3.441). Mothers with positive history of PTB in any of previous pregnancy was 10.7 times more likely to have early PTB in current pregnancy (P-value: <0.001, COR: 10.677, 95% CI: 2.792 – 40.746). Both variables were found to have independent risk on early PTB in logistic regression analysis (education: P-value: 0.027, aOR: 2.973, 95% CI: 1.132- 3.047; previous history of PTB: P-value: 0.002, aOR: 9.191, 95% CI: 2.308 - 36.596). Early and late PTB have differential risk factors. Mothers with positive history of PTB and having lower level of education were more likely to have early PTB.